2007
DOI: 10.1038/sj.sc.3102056
|View full text |Cite
|
Sign up to set email alerts
|

Subacute progressive ascending myelopathy following spinal cord injury: MRI appearances and clinical presentation

Abstract: Study design: Retrospective Case Review. Objectives: To describe the clinical presentation and course of patients with magnetic resonance imaging (MRI) features of subacute progressive ascending myelopathy (SPAM). A rare complication of spinal cord injury. Setting: National Spinal Injuries Centre, Stoke Mandeville Hospital, UK. Materials and methods: A retrospective review of the case notes and MRI studies of 11 cases with typical MRI features of ascending myelopathy presenting to a tertiary Spinal Injuries ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 19 publications
(27 reference statements)
2
88
1
Order By: Relevance
“…Subacute progressive ascending myelopathy has an associated mortality of up to 10%, although the majority of patients spontaneously improve but rarely regain all of the lost function. 28 Lee et al 32 reported good recovery with cord untethering and duroplasty.…”
Section: Cord Oedemamentioning
confidence: 99%
See 1 more Smart Citation
“…Subacute progressive ascending myelopathy has an associated mortality of up to 10%, although the majority of patients spontaneously improve but rarely regain all of the lost function. 28 Lee et al 32 reported good recovery with cord untethering and duroplasty.…”
Section: Cord Oedemamentioning
confidence: 99%
“…28,29 The clinical picture is typically one of deterioration in the patient's motor score and an ascending sensory level, although the condition can remain subclinical. This is also described as progressive posttraumatic myelomalacic myelopathy.…”
Section: Cord Oedemamentioning
confidence: 99%
“…9,10 Obvious cerebrospinal fluid pressure (CSFP) elevation has been shown after SCI in preclinical and clinical studies, [11][12][13] and CSFP elevation may lead to neurological dysfunction. 14 Meagher et al 15 and Planner et al 2 reported that disruption of CSF dynamics was the major cause of SPAM. In an SCI animal model, Jones et al 16 found that an enlarged cord immediately occluded the subarachnoid space in severe SCI, and CSF pressure was only partially decreased by epidural decompressive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological confirmation with MRI is an important criterion for the diagnosis of SDAM. 4 The role of other imaging modalities, such as FDG-PET, in the assessment of SDAM remains unclear.…”
Section: Radiological Featuresmentioning
confidence: 99%